Effects of a Short Educational Program for the Prevention of Foot Ulcers in High-Risk Patients: A Randomized Controlled Trial - Matteo Monami; Stefania Zannoni; Marianna Gaias; Besmir Nreu; Niccolò Marchionni; Edoardo Mannucci (International Journal of Endocrinology)
Background. Patient education is capable of reducing the risk for diabetic foot ulcers. However, specific education on foot ulcer prevention was either included in broader programs addressing different parts of diabetes care or provided with time- and resource-consuming curricula. The aim of the study is to assess the feasibility and efficacy of a brief educational program for the prevention of diabetic foot ulcers in high-risk patients. Methods. The study was performed on type 2 diabetic patients, randomized in a 1 : 1 ratio either to intervention or to control group. The principal endpoint was the incidence of foot ulcers. The intervention was a two-hour program provided to groups of 5–7 patients, including a 30-minute face-to-face lesson on risk factors for foot ulcers, and a 90-minute interactive session with practical exercises on behaviors for reducing risk. Results. The study was prematurely terminated due to a highly significant difference in outcome between the two treatment groups. The final sample was therefore composed of 121 patients. Six patients, all in the control group, developed ulcers during the 6-month follow-up (10% versus 0%, p=0.012). Conclusions. A brief, 2-hour, focused educational program is effective in preventing diabetic foot ulcers in high-risk patients.